POLA SEBARAN USAHA MIKRO KECIL MENENGAH (UMKM) KULINER KEMASAN KHAS MINANG DI KOTA PADANG BERBASIS WEBGIS - CHICI SARTIKA AYU; Rery Novio (JURNAL BUANA, 2023)
ABSTRACTThe research objectives: 1) The distribution pattern of packaged culinary SMEs of Minang, 2) Classification of packaged culinary SMEs on Capital, Raw Materials, Labor and Sales and Marketing 3) Distribution of packaged culinary SMEs in Padang District, Padang City using Webgis. This research is a quantitative descriptive research using neighbor nearst analyst analysis techniques, percentage descriptive, cross tabulation and WebGIS distribution. The results of this study: 1) The distribution pattern of Minang Typical Culinary MSMEs in West Padang District which was analyzed with the Average Nearest Neighbor in the ArcGIS Application obtained a Nearest Neighbor Ratio value of 0.743437, then the distribution pattern of MSME Culinary Packaging Typical Minangan has a Clustered pattern. . 2) Classification of Packaged Culinary MSMEs in West Padang District, Padang City based on profile, capital, raw materials, labor and sales & marketing according to PP MSME NO. 7 of 2021, the type of MSMEs of typical Minang culinary packaging as many as 37 MSMEs are still active in the District West Padang, the classification is Micro Enterprises. 3) The distribution of Minang typical packaged culinary SMEs in Padang Barat District, Padang City seen from the WebGis shows the location points as well as provides information related to the distribution of MSMEs totaling 37 MSMEs, to make it easier for local residents, local tourists and foreign tourists to find locations so as not to make it difficult for buyers to find out the location of MSMEs with a running application.Keywords: MSME Distribution Pattern, Nearest Neighbor Ratio, WebGIS